Analisis Kelayakan Usaha Alpukat dalam Pot di Desa Wisata Jambu Kabupaten Kediri - Fauzan, Muhammad Bishma; Artini, Widi; Sidhi, Eko Yuliarsha; Satriya Bayu Aji; Djoko Rahardjo (Universitas Kadiri, 2025)
Avocado Kelud cultivation in Jambu Tourism Village, Kediri Regency, using the Tabulampot technique (fruit plants in pots), shows great potential as an agribusiness. This training aims to analyze the financial feasibility of the farming business by highlighting the main problems, such as the limitations of optimal application of the Tabulampot technique and the lack of research on its financial feasibility. Data were obtained from farmers' financial records during 2024 through a purposive sampling method. The analysis was carried out to calculate production costs, income, and financial feasibility indicators, such as Break-Even Point (BEP), Revenue-Cost Ratio (R-C Ratio), and Benefit-Cost Ratio (B-C Ratio). The results showed a total production cost of IDR 18,705,815, resulting in a total income of IDR 51,041,250 with a net profit of IDR 32,335,435. BEP was recorded at IDR 19,108 per kilogram, far below the selling price of IDR 45,000 per kilogram. The R-C Ratio value of 2.97 and B-C Ratio of 1.72 indicate that this business is efficient and profitable. This study emphasizes the importance of innovative marketing strategies, production cost management, and optimization of Tabulampot techniques to maintain product competitiveness in the premium market. This study provides practical recommendations for farmers and stakeholders to increase the productivity and sustainability of Tabulampot-based agribusiness, which can become a model for sustainable farming. Budidaya Alpukat Kelud di Desa Wisata Jambu, Kabupaten Kediri, menggunakan teknik Tabulampot (tanaman buah dalam pot) menunjukkan potensi besar sebagai usaha agribisnis. Penelitian ini bertujuan untuk menganalisis kelayakan finansial usaha tani tersebut dengan menyoroti permasalahan utama, seperti keterbatasan penerapan teknik Tabulampot secara optimal dan minimnya penelitian mengenai kelayakan finansialnya. Data diperoleh melalui metode purposive sampling dari catatan keuangan petani selama tahun 2024. Analisis dilakukan untuk menghitung biaya produksi, pendapatan, serta indikator kelayakan finansial, seperti Break-Even Point (BEP), Revenue-Cost Ratio (R-C Ratio), dan Benefit-Cost Ratio (B-C Ratio). Hasil menunjukkan total biaya produksi sebesar Rp18.705.815 menghasilkan total pendapatan Rp51.041.250 dengan keuntungan bersih Rp32.335.435. BEP tercatat sebesar Rp19.108 per kilogram, jauh di bawah harga jual Rp45.000 per kilogram. Nilai R-C Ratio sebesar 2,97 dan B-C Ratio sebesar 1,72 mengindikasikan bahwa usaha ini sangat efisien dan menguntungkan. Studi ini menekankan pentingnya strategi pemasaran inovatif, pengelolaan biaya produksi, dan optimalisasi teknik Tabulampot untuk mempertahankan daya saing produk di pasar premium. Penelitian ini memberikan rekomendasi praktis bagi petani dan pemangku kepentingan untuk meningkatkan produktivitas dan keberlanjutan agribisnis berbasis Tabulampot, yang berpotensi menjadi model usaha tani berkelanjutan.